Postural control in Tunisian soccer players - Zouita Ben Moussa, A.; Zouita, S.; Dziri,C.; Ben Salah, F. Z. (Science & Sports, 2012)
Summary: The relation between the contribution of vision and the expertise level on postural control appears to depend on the sport practised. The purpose of our work is to analyse the postural control and the use of visual information in soccer players according to their level of competition. Methods: Two groups of healthy soccer players were investigated: an amateur (AM) (n = 16) group composed of regional-level players and a professional group at a national level (PRO) (n = 16). Posture was assessed by measuring the center of gravity velocity (COG) with a force platform "Balance Master®" during a test (30 s) of bipedal and single-leg stance quiet standing posture. Results: The COG velocity was significantly greater in the AM group than in the PRO group with EO and EC. The vision and surface factors engendered significant differences in both the AM and PRO groups (P < 0.05). Indeed, on souple surface EO condition, sway of COG was greater for the AM group than for the PRO group (P < 0.05). Conclusion: The contribution of vision in postural maintenance was less important in the PRO players than in the AM players.